SUB’HAA - Harisnal Hadi (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
Sub'haaThe preparation of the artwork entitled "Subhaa", is inspired by the Minangkabau cultural phenomenon. This work focuses on the feelings of children who will be circumcised, the pressure and fear felt by the child who will be circumcised tilled in the form of Polymetrik art works. Circumcision or commonly called Basunaik by Minangkabau society is a Sunna that must be run boys of Islam; indirectly circumcision is also required for boys in Minangkabau. In the area of darek (mainland) khitan has its own ceremony, begins with a child who will be circumcised is brought to the bako house to change his clothes, then paraded around the village, after arriving at home circumcised will be held. In the evening there will be entertainment in the form of randai and bagurau saluang. This piece of music is in the form of a new composition. The performance focuses more on the composition of sound as a contextual meaning to be conveyed to the appreciator. This work is a little contrary to the aesthetics that have been awakened in the brain and soul of the arts in the Sendratasik Department of FBS Universitas Negeri Padang. But it cannot be denied that a new works will create its own aesthetic realm. Keywords: Basunaik, Artwork Music. Abstrak Penyusunan karya seni yang berjudul “Subhaa”, ini terinspirasi dari fenomena budaya Minangkabau. Karya ini menitik beratkan garapan pada perasaan anak yang akan dikhitan, tekanan dan ketakutan yang dirasakan oleh anak yang akan dikhitan digarap dalam bentuk penggarapan Polymetrik. Khitan atau biasa disebut Basunaik oleh masyarakat Minangkabau merupakan sunah yang harus dijalankan anak laki-laki Islam, secara tidak langsung khitan juga diwajibkan bagi anak laki-laki di Minangkabau. Di daerah darek (daratan) khitan memiliki upacara tersendiri, diawali dengan anak yang akan dikhitan dibawa ke rumah bako untuk mengganti baju, lalu diarak keliling kampung, setelah sampai di rumah baru diadakan khitan, malamnya diadakan hiburan berupa randai dan bagurau saluang. Karya musik ini berbentuk komposisi garapan baru. Penggarapan lebih menitik beratkan kepada penggarapan bunyi sebagai makna kontekstual yang akan disampaikan kepada apresiator. Karya ini memang sedikit bertolak belakang dengan estetika yang sudah terbangun dalam otak dan jiwa kalangan seni di jurusan pendidikan sendratasik FBS Universitas Negeri Padang. Namun tidak bisa dipungkiri sebuah karya garapan baru akan menciptakan ranah estetikanya sendiri.Kata Kunci: Basunaik, Karya seni Musik.